The Green storytelling marketing: influencing consumer purchase decision through environmental consciousness - Lauwrensia, Anastasia Pratiwi; Ariestya, Angga (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
This research examines marketing on social media using green storytelling, especially on green products such as product of composting. In the green storytelling marketing activity, stories about composting activities at home are shown to eradicate the problem of organic waste and promoting product of composting. It is interesting because currently organic waste is the most common type of waste in Indonesia. This research uses a quantitative method for followers of the Instagram account @Sustaination (N=338). Participants are account followers who have purchased composter products and carried out composting activities. An interesting finding in this study is that green storytelling marketing activities can have a direct influence on purchasing decisions for composter products. In addition, the influence of green storytelling marketing can also affect on purchase decision through environmental consciousness. This is because green storytelling marketing can affect the affective, cognitive, and dispositional dimensions of environmental consciousness. In green storytelling marketing, there is information and knowledge conveyed through the stories displayed. This can then help influence the active dimension in which there is an element of purchasing green products. This is the reason green storytelling marketing through environmental consciousness can influence the purchase decision of composter products.